Macrostomum shenda and M. spiriger, two new brackish-water species of Macrostomum (Platyhelminthes: Macrostomorpha) from China - Xin, Fan; Zhang, Si-Yu; Shi, Yong-Shi; Wang, Lei; Zhang, Yu; Wang, An-Tai (Zootaxa, 2019)
In this study, two new brackish-water species of Macrostomum (M. shenda n. sp. and M. spiriger n. sp.) collected from Shenzhen, China, were described based on morphological, histological, and molecular phylogenetic analyses. Macrostomum shenda n. sp. differs from its congeners in the oblique and non-thickening distal opening of its narrow funnel-shaped stylet. In addition, its sperm have neither bristles nor brush, and are surrounded by an undulating membrane in the mid-body region. In M. spiriger n. sp., the stylet is spirally twisted. Its reproductive apparatus has a seminal bursal pore opening exteriorly. Results of the 18S and 28S rDNA phylogenetic analyses also support the establishments of these two new species. Moreover, the 18S and 28S rDNA sequences of some species within Macrostomum in previous studies have been revised to avoid ambiguity, while Macrostomum dongyuanensis Wang & Sun, 2015 was re-identified as a new record of M. quiritium Kolasa, 1973 from China.